Can You Hear My Heartbeat?: Hearing an Expressive Biosignal Elicits Empathy - Winters, R. Michael; Walker, Bruce N.; Leslie, Grace (2021 Human Factors in Computing Systems, 2021)
Interfaces designed to elicit empathy provide an opportunity for HCI with important pro-social outcomes. Recent research has demonstrated that perceiving expressive biosignals can facilitate emotional understanding and connection with others, but this work has been largely limited to visual approaches. We propose that hearing these signals will also elicit empathy, and test this hypothesis with sounding heartbeats. In a lab-based within-subjects study, participants (N = 27) completed an emotion recognition task in different heartbeat conditions. We found that hearing heartbeats changed participants’ emotional perspective and increased their reported ability to “feel what the other was feeling.” From these results, we argue that auditory heartbeats are well-suited as an empathic intervention, and might be particularly useful for certain groups and use-contexts because of its musical and non-visual nature. This work establishes a baseline for empathic auditory interfaces, and offers a method to evaluate the effects of future designs.